2022
DOI: 10.3389/fcimb.2022.935681
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture ameliorates peptic ulcer disease in association with gastroduodenal microbiota modulation in mice

Abstract: Peptic ulcer disease (PUD) is a common disease and frequently encountered in the clinic. Accumulating evidence suggests that PUD is associated with the gastrointestinal microbiota. Electroacupuncture (EA) is an improved version of acupuncture, which can improve the clinical effect by increasing the stimulation and delivering appropriate electrical pulses to needles. This method has been widely used in the treatment of peptic ulcer disease. However, its effect on gastrointestinal microbiota remains unclear. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The dysfunctional intestinal microflora can stimulate inflammatory response, change the intestinal mucosal permeability, affect the inflammatory factors to aggravate the cerebral ischemia injury, and then feed back to the gut and microflora, and the cycle repeats. Acupuncture and moxibustion can regulate the various links of the cerebral and intestinal axis and block this vicious cycle (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…The dysfunctional intestinal microflora can stimulate inflammatory response, change the intestinal mucosal permeability, affect the inflammatory factors to aggravate the cerebral ischemia injury, and then feed back to the gut and microflora, and the cycle repeats. Acupuncture and moxibustion can regulate the various links of the cerebral and intestinal axis and block this vicious cycle (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…According to existing studies, acupuncture can treat diseases by conducting information exchange between immune-neuro-endocrine-microbial metabolism through brain-intestinal interaction ( Xu and Lu, 2020 ). For example, acupuncture affects the abundance and structure of intestinal bacteria, balancing the number and proportion of probiotics and pathogens in the host body ( Xie et al, 2020 ; Wang J. M. et al, 2021 ; Wang T. Q. et al, 2021 ; Li et al, 2022d ). In turn, acupuncture reverses a variety of intestinal flora metabolic disorders caused by various diseases by restoring the function and metabolic pathway of key metabolites in human body ( Xu et al, 2017 ; Si et al, 2022 ).…”
Section: The Relationship Between Acupuncture and Intestinal Microbiotamentioning
confidence: 99%
“… Li et al (2022d) detected the diversity and richness of microflora in the stomach and duodenum after electroacupuncture, as well as the content changes of VIP, DA, and trilobal factor (TFF) in serum. Researchers found that electroacupuncture increased TFF and DA levels in the serum, as well as the diversity and richness of stomach microbiota.…”
Section: Acupuncture Regulates Intestinal Microbiota In Psdmentioning
confidence: 99%
“…While these acupuncture points also have distal effects based on the traditional meridian, such as the LI10 to treat diseases in the large intestine and other digestive systems. Recent study showed that in mice with peptic ulcer disease, electroacupuncture in LI10 resulted to a significant reduce in the injury of the gastroduodenal mucosa and an increase in the diversity of gastric microbiota ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%